Green leviathan the case for a federal role in environmental policy - Weibust, Inger (Federalism studies, 2016)
The US, Switzerland and Canada are wealthy democracies that should be conducive to effective decentralized or cooperative environmental policy-making. However, a closer examination of their environmental policy over many decades finds no evidence that these approaches have worked. So does it matter which level of government makes policy? Can cooperation between sub-national governments protect the environment? Building on comparative case studies on air and water pollution and making use of extensive historical material, Inger Weibust questions how governance structure affects environmental policy performance in the US, Switzerland, Canada and the European Union. The research breaks new ground by studying formal and informal environmental cooperation. It analyzes whether federal systems with more centralized policy-making produce stricter environmental policies and debates whether devolution and the establishment of subsidiaries will lead to less environmental protection. An essential insight into the complexities of policy-making and governance structures, this book is an important contribution to the growing debates surrounding comparative federalism and multi-level governance.